Role of Innovation Management Practices in Enhancing Firm Agility and Adaptability during Times of Crisis in Turkey - Azra, Aydin (International Journal of Strategic Management, 2023)
Purpose: The study sought to investigate the role of innovation management practices in enhancing firm agility and adaptability during times of crisis in Turkey. Materials and Methods: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library Findings: The study found that Turkish firms embracing innovation management practices exhibited enhanced agility and adaptability during crises. These practices included nurturing an innovative culture, investing in research and development, and embracing digital solutions. Leadership commitment and external collaborations were identified as crucial enablers. Additionally, the research underscored the importance of tailoring strategies to Turkey's specific context to effectively bolster firm resilience during challenging times. Unique Contribution to Theory, Practice and Policy: The study recommends Turkish firms should formulate agile innovation strategies that emphasize flexibility and rapid response to changing market conditions. This involves regularly assessing customer needs, market trends, and emerging technologies. By continuously adapting their innovation strategies, firms can remain responsive and agile during crises. This recommendation contributes to theory by emphasizing the integration of agility principles into innovation management frameworks, highlighting the need for dynamic and iterative approaches. Encourage cross-functional collaboration within organizations to facilitate innovation.